Substitution Effects of Nickel and Cobalt in WC Based Hard Metal - Alizadeh, E. (Asian Journal of Chemistry, 2010)
In the present work, the effects of partial and complete substitution of cobalt by nickel in some WC-10% binder phase hard metals have been investigated.